Effects of Remuneration on Employee Turnover in Private Hospitals Samburu County - Lekartiwa, Haron; Rintari, Nancy; Moguche, Abel (Human Resource and Leadership Journal, 2020)
Purpose: The purpose of this study was to investigate the effects of Remuneration on employee turnover in private hospitals Samburu County. Methodology: This study adopted descriptive survey research design and was conducted in ten private hospitals in Samburu County. Information was issued by 71 medical practitioners such as senior doctors, senior nurses, senior pharmacists and senior medical technologists of each of the private hospitals in Samburu county. The71 medical practitioners were sampled using convenience sampling methods because medical practitioners in a hospital setting were generally very busy hence data was collected through closed ended questionnaires from the available ones. Linear regression was used to test each hypothesis while multiple regression analysis was used to measure the effects of renumeration on employee turnover in private hospitals Samburu County. The analysis was later presented using tables and detailed explanations. Results: The study discovered that there was a positive relationship and statistically significant between that renumeration and employee turnover. That simply explained meant that how employees are rewarded at the end of the agreed contract duration or at the end of the month play a very key part in determining whether they will leave in the near future or not. Poor and inconsiderate renumeration will often make them want leave and look for other better paying ventures. Unique contribution to theory, policy and practice: Human resource managers should ensure that renumeration structure is reviewed where employees receive all the benefits gotten at various job groups without biasness. Once an employee attains the required qualifications, they should automatically be enrolled to the improved renumeration structure without too much bureaucracies. This will motivate employees to work harder so as to attain their personal goals in the job ladder. Future researchers should aim to concentrate on other regions in Kenya to determine whether renumeration will be the key causal determinant on employee turnover.